Syiar Di Media Massa: Potret Dakwah Organisasi Muhammadiyah dalam Majalah Adil Tahun 1974-1979: Broadcasting in the Mass Media: Portrait of Muhammadiyah Organization Da'wah in Adil Magazine 1974-1979 - Ayu Kartika Dewi, Irma; Nur Khikmah , Khoirina (Journal of Islamic History, 2022)
This paper discusses the development of the da'wah of the Muhammadiyah Islamic organization in Adil Magazine in 1974-1979. This study aims to determine the characteristics of Muhammadiyah's da'wah in Adil Magazine in 1974-1979 and to determine the role of Muhammadiyah's da'wah as portrayed in the 1974-1979 Adil Magazine. This research is a historical research by looking for facts of past events. This research is included in the research type of literature review, through four stages, namely heuristics (data collection), source criticism, interpretation, and histography. The results showed that the development of Muhammadiyah on the island of Java was quite rapid, marked by the publication of Adil Magazine on October 1, 1932 in Surakarta. Adil Magazine publishes news, articles, and advertisements that are useful for readers of the general public and upper middle class. Adil Magazine played a role in spreading Muhammadiyah teachings. Readers can know and study Islamic laws and other religious ways. Adil Magazine is divided into several rubrics, namely Da'wah Rubric, Social Rubric, the Actual Events Rubric and Womanhood Rubric.